Frontiers in catecholamine research : proceedings - Usdin, Earl; Snyder, Solomon H., 1938- (Pergamon Press, 1973)
Frontiers in Catecholamine Research is a collection of papers presented at the Third International Catecholamine Symposium, held at the University of Strasbourg, Strasbourg, France, on May 20-25, 1973.